The Role Of Self-Management In Increasing Subjective Well-Being Of DKI Jakarta’s Citizens - Takwin, Bagus; Singgih, Evita Eddie; Panggabean, Sahat Khrisfianus (UI Scholars Hub, 2012)
Big cities are characterized by their dense population, limited space, and high mobility. Past research has shown that the citizens of DKI Jakarta feel quite unhappy. Therefore it is necessary to improve the happiness (subjective well-being) level of DKI Jakarta’s population. Subjective well-being relates to how an individual self-manages his/her activities. Individuals with good subjective well-being tend to engage in activities of high productive values. This research aims to understand the role of self-management in the subjective well-being of the population of DKI Jakarta. 638 citizens of DKI Jakarta (males = 329, females = 309; mean age = 36) participated in the study. Data was collected through five sets of questionnaires, i.e., the satisfaction with life scale (SWLS), the positive affect and negative affect schedule scale (PANAS), The domains of life satisfaction scale, self-management questionnaire, and the demograhic questionnaire. Analysis of data using multiple regression confirmed that self-management is positively associated with life satisfaction (R = 0.391, p = 0.05) and positive affects (R = 0.108, p = 0.05).